A grounded theory of the Kenya human interaction model for mental health nursing practice - Wagoro, Miriam Carole Atieno (Department of Health and Rehabilitation Sciences, 2017)
Background: Although mental disorders is of great public health concern among Kenyan populations, mental health services remain poor. Some of the reasons attributed to delivery of poor mental health services are unfavourable work environment and lack of policy guidelines including a conceptual model of nursing.Quality of mental health nursing care significantly impacts on general mental health services in Kenya since they are predominantly provided by nurses. Lack of a model to guide care and improve mental health services created the need to develop the Kenyan Human Interaction Model for mental health nursing practice. Purpose: The purpose of the study was to discover and develop a Kenyan model for mental health nursing guided by two research questions, namely: What are the views of Kenyan mental health nurses with regards to human being, environment, mental health nursing and mental health: What is the appropriate model for mental health nursing practice in Kenya? Methodology: Straussian Grounded Theory method was used in the study. Data were collected for 6 months through in-depth interviews with 33 registered mental health nurses selected by open, purposive and theoretical sampling methods. Inductive and deductive data analysis of the nurses' description of their views and recommendations on the nursing metaparadigms were done Findings: A substantive theory of the Kenyan Human Interaction Model for mental health nursing practice was developed .The four metaparadigm concepts of the discovered theory are: 1. Human being as a unique biopsychosocio-spiritual being and causal condition 2. Environment consisting of homely and hostile dimensions 3. Mental health nursing as a holistic care founded on human interaction 4. Mental health (consequence of holistic care) with optimum and illness dimensions. Mental health nursing was discovered as the central phenomena interacting with its causal, contexts and intervening conditions to determine the mental health dimension of the human being. The quality of mental health nursing determines the mental health dimensions and is influenced by the environment and nurses' characteristics as contexts and intervening conditions respectively. These interactions lead to consequences discovered as optimum mental health. The Kenya Human Interaction Model for mental health nursing practice is customized to the Kenyan situation and contributes knowledge which is relevant to mental health nursing practitioners, students, educators and administrators.